(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
The purpose of the research is to identify and analyze the peculiarities and problems of theory and practice teaching methods of virology courses in the higher education system. The professional literature related to the topic has been studied, the necessity and importance of a substantive revision of virology teaching methods in the higher education system have been substantiated, the ways to overcome existing difficulties have been suggested. A combination of both traditional lecturer-centered and innovative student-centered interactive approaches to course delivery have been substantiated. In order to ensure the end results arising from the course goal, it is necessary to supplement the teaching of the subject with the use of laboratory work involving modern sensitive and accurate methods. The course outcomes should provide the student with adequate knowledge and understanding of viruses, analysis and synthesis skills, the ability to evaluate and comprehensively solve the proposed professional problems.